IoT Implementation in Various Applications: A Detailed Review of Cyber Security Issues and Challenges - Lourens, Melanie; Gangodkar, Durgaprasad; Tiwari, Mohit; Buddhi, Dharam; Dharamvir, Dharamvir; Kuchhal, Shikha (2023 3rd International Conference on Advance Computing and Innovative Technologies in Engineering (ICACITE), 2023)
Data must be protected against cybercrime as the network revolution grows and becomes more complicated. With the purpose to intentionally damage sensitive and secret information, cybercrimes cost the world economy billions of dollars. Because these crimes are perpetrated often, it is vital to increase cyberspace security to lessen and perhaps even prevent the effects of cybercrime. The internet of things (IoT) phenomena is now the subject of study, as privacy and safety are acknowledged as the primary concerns for Iot., particularly in light of the fact that they are being used in crucial contexts like healthcare systems. The current state of safety in the IoT sector is examined in this paper, along with security-related problems. We look at particular security needs and methods for resolving these problems. IoT safety is being recognised as a problem that blockchains may help with.